A Novel Microchip Flow Chamber (Total Thrombus Analysis System) to Assess Canine Hemostasis - Iwanaga, Tomoko; Miura, Naoki; Brainard, Benjamin M.; Brooks, Marjory B.; Goggs, Robert (Frontiers in Veterinary Science, 2020)
Hemorrhagic diseases are common in dogs. Current coagulation assays do not model all aspects of in vivo hemostasis and may not predict bleeding risk. The Total-Thrombus Analysis System (T-TAS) is a novel hemostasis assay system in which whole blood flows through microfluidic channels at defined shear rates to provide qualitative and quantitative evaluation of platelet function (PL-chip) and coagulation function (AR-chip). The present study evaluated the T-TAS in dogs with hereditary bleeding disorders and with acquired hemorrhagic syndromes (Group 1), and healthy controls (Group 2). Hereditary defects included von Willebrand’s disease (VWD; n=4), hemophilia A (n=2), and canine Scott syndrome (n=2). Acquired hemorrhagic disorders included neoplastic hemoperitoneum (n=2) and acute hemorrhagic diarrhea syndrome (n=1). Citrate anticoagulated samples were collected from diseased dogs (Group 1, n=11) and controls (Group 2, n=11) for coagulation screening tests, fibrinogen analyses, D-dimer concentration, antithrombin activity, von Willebrand Factor antigen, PFA-100 closure time (PFA-CT) and thromboelastography (TEG). Citrate and hirudin anticoagulated samples were used for T-TAS analyses at two shear rates. Qualitative thrombus formation in each chip was recorded using the T-TAS video camera. Numeric parameters, derived from the instrument software, included occlusion start time (OST; time to 10kPa), occlusion time (OT; time to 60kPa (PL-chip) or 80kPa (AR-chip)), and area under the pressure curve (AUC). Correlations between continuous variables were evaluated by Spearman’s rank. Continuous variables were compared between groups by Student’s t-test or the Mann-Whitney U test. Alpha was set at 0.05. In combined analyses of all dogs, significant correlations were identified between T-TAS variables, between the PFA-CT and PL-chip parameters and between TEG variables and AR-chip parameters. The prothrombin time correlated with the AR-chip AUC at both shear rates. In Group 1 dogs, the AR-chip AUC at low shear was significantly reduced compared with Group 2 dogs. Aberrant thrombus formation was seen in video images recorded from dogs with VWD and hemophilia A. The T-TAS AR-chip analysis distinguished dogs with bleeding risk compared to healthy controls. Initial evaluations of the T-TAS suggest it may aid characterization of hemostasis in patients at-risk of bleeding and assist with delineating bleeding phenotypes.